Investigations on copper nano-particles synthesis by pulsed electrochemical dissolution (PECD) process - Alam, Muneer; Jain, Neelesh Kumar; Pathak, Sunil (2018)
This article reports on development of a simple and cost effective electrolytic synthesis of copper nanoparticles using copper sulphate as metal precursor. An in-house setup of pulsed-electrochemical dissolution (PECD) process for the synthesis of nano-particles has been conceptualized and developed. Generated nano-particles were characterized using X-ray diffraction (XRD), scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDX) to analyze the crystal size, morphology and chemical composition of the particles. Experiments were conducted in two phases, namely pilot and main experiments. The pilot experiments were done to study the effects of electrolyte concentration, inter electrode gap (IEG) and processing time on the nano-particles shape and size. Average minimum size of the particles obtained during the pilot experiments were found to be 150 nm at identified optimum parameters i.e. 5 wt.% as electrolyte concentration; 30 minutes as processing time; and 10 mm as IEG. These identified optimum values of the input parameters were used during the main experiments. The main experiments were conducted to optimize the values of applied voltage, pulse-on time and pulse-off time. Average minimum size of the particles obtained during the main experiments was found to be 70 nm at the identified optimum value of the parameters; 8 V as voltage; 4 ms as pulse-on time and 8 ms as pulse-off time.